Insight into the selenoproteome of the malaria parasite Plasmodium falciparum - Röseler, Anne; Schirmer, Rolf Heiner (Antioxidants & redox signaling, 2012)
Aims: The malaria parasite Plasmodium falciparum possesses four unique selenoproteins (PfSel1-PfSel4) which are likely to represent important components of the redox-regulatory network of this infectious agent. So far these proteins have only been characterized in silico. The aim of the present study was to gain further insight into the structural, biochemical, and functional properties of P. falciparum selenoproteins. Results: Using 75Se labeling in P. falciparum cell culture, the presence of selenoproteins in the parasite could be verified for the first time. Bioinformatic analyses indicated distant relatedness between the Plasmodium proteins and selenoproteins described in other organisms, namely between PfSel1 and SelK, PfSel2 and SelT, and between PfSel4 and SelS. For PfSel3 no remarkable similarities with proteins from other organisms were identified. All four proteins were recombinantly produced in Escherichia coli as UGA→UGU (selenocysteine→cysteine) mutants. Using green fluorescent protein (GFP)-fusion proteins and immunofluorescence, the subcellular localization of the four selenoprotein mutants was studied. PfSel1, PfSel2, and PfSel4 localized to the endoplasmic reticulum whereas PfSel3 was visualized in the nucleus and/or the apicoplast. Functional assays support the roles of PfSel1 and PfSel4 in cellular redox reactions. Transcriptional profiles of the four selenoproteins, and proteins involved in selenoprotein biosynthesis, indicate that their expression is regulated via the availability of selenium and via oxidative and nitrosative stress. Innovation: In this study the presence of selenoproteins in Plasmodium has been proven for the first time; the subcellular localization of the proteins and their relatedness to known selenoproteins have been systematically studied, and recombinant proteins as well as information on regulation of transcript levels have been obtained. Conclusion: Taken together, our data enhance our understanding of the functional role of selenoproteins in Plasmodium. Antioxid. Redox Signal. 17, 534-543.